Perencanaan Jaminan Mutu di Madrasah Aliyah Nuurul Qur'an Bogor - Abdullah Mizan; Maemunah Sa’diyah; Nisrina Khairunnisa Supriatna; Nunuy Nurjanah; Muhammad zaki tamami (At Turots: Jurnal Pendidikan Islam, 2024)
Quality Assurance Planning at Madrasah Aliyah Nuurul Qur'an Bogor Educational quality assurance planning focuses on the processes in the system of achieving the goals of a school organization. This writing aims to examine the stages of effective quality assurance planning in schools and innovate quality assurance planning at Madrasah Aliyah Nuurul Qur'an Bogor. The method used is qualitative with data collection carried out by interviews, observation, Focus Group Discussion (FGD), research participants namely the Head of the Madrasah, Deputy Head of the Madrasah for Curriculum and Student Affairs, teachers and parents. School quality assurance planning is carried out to be able to carry out situation analysis and identify problems, this can make it easier for organizations to determine the root of the problem and be able to resolve various existing problems with minimal obstacles. For this reason, it is necessary to carry out various strategic plan innovations to improve the quality assurance of Islamic education in current conditions, including by making curriculum adjustments, formulating curriculum achievement targets based on the characteristics of students and the educational environment. Compiling learning materials according to students' level of thinking in the era of globalization and current needs. Apart from that, important monitoring and budgeting is also needed in collaboration with the government to provide confirmation of the necessary support based on needs analysis so that madrasah quality assurance planning is better according to its potential.